Actualización de los recursos bibliográficos y tecnológicos en la biblioteca de la unidad educativa Federico González Suárez, del cantón Alausí y su incidencia en la satisfacción de las necesidades de información de sus usuarios, periodo lectivo 2013-2014 - Ortiz Mora, Miriam Patricia (2014)
This thesis called “UPDATE BIBLIOGRAPHIC RESOURCES AND TECHNOLOGY IN THE LIBRARY OF EDUCATION UNIT FEDERICO GONZALEZ SUAREZ, ALAUSI CANTON AND ITS IMPACT ON THE SATISFACTION OF THE INFORMATION NEEDS OF ITS USERS, school period 2013-2014”, is structured and developed in accordance with current regulations of the National University of Loja. The overall objective was: To analyze the updating of bibliographic and technological resources of the Library of the "Federico González Suárez”, Education Unit affect meeting the information needs of users. The methods that use was made were Scientist, Analytical - Synthetic, Inductive - Deductive, Descriptive; and Statistical Model, the same that were used to describe and explain how the update of bibliographic and technological resources affect the satisfaction of user needs. The technique used was a survey: Applied to Directing Staff Federico González Suárez” Education Unit, to collect information about the update for Bibliographic Resources and Technology Library. And a survey of users of the Library of Federico González Suárez Education Unit, in order to measure the degree of satisfaction of information needs. According to the survey applied to users. 46% said Bibliographic Resources which owns the "No" Library meets their information needs, 29% indicated that sometimes and 25% of users answered "Yes". The results of the Survey on the Directing Staff "Federico González Suárez" Educational Unit. 100% state that the update of the bibliographic and technological resources affect whether meeting the needs of users.